Halloysite / zirconium phosphate nano composite material, preparation method thereof and application of halloysite / zirconium phosphate nano composite material in heavy metal adsorption
By growing nano -phosphate particles on the inner wall of Ellow nano tube, the problem of poor stability and distribution uniformity of nanoparticles is solved, and high -efficiency heavy metal ion adsorption and multiple cyclic utilization are achieved.
Patent Information
- Application Number
- CN202411485489.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, the stability of the surface-loaded nanoparticles of Elosite nanotubes is poor, making it difficult to achieve in-situ growth and multiple recycling of nanoparticles, and zirconium phosphate nanoparticles are difficult to uniformly distribute and exist stably on the carrier material.
By growing nano -phosphate particles in situ on the inner wall of Ellow nano tube, using the lumen space restriction effect of Ellow nano tube, regulating the size and distribution of phosphate particles, and using vacuum -assisted preparation methods to ensure the phosphate particles particles particle particles Uniformity and stability.
The uniform distribution and stable existence of zirconium phosphate nanoparticles are achieved, the adsorption activity and recycling performance of the composite material are improved, and the selective adsorption capacity of heavy metal ions is enhanced.
Smart Images

Figure CN119346064A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an adsorption material, in particular to a halloysite / zirconium phosphate nanocomposite material, and also to a preparation method of the halloysite / zirconium phosphate nanocomposite material and application of the halloysite / zirconium phosphate nanocomposite material in heavy metal ion adsorption, belonging to the technical field of materials. Background Art
[0002] Halloysite nanotubes (HNTs) are natural clay materials formed by the inward curling of kaolin sheets. They have a unique hollow tube structure, with an outer surface composed of siloxane (Si-O-Si) groups and an inner cavity composed of aluminum alcohol (Al-OH) groups, which can be selectively loaded and modified inside and outside the tube. At present, there are reports on the assembly of nanoparticles on the surface or inner wall of HNTs. For example, the literature ("A ferroptosis-targeting ceria anchored halloysite as orally drug delivery system for radiation colitis therapy", Rong-rong He, et al., Nature Communications, 2023-08-22) uses the negatively charged surface of halloysite nanotubes to attract Ce ions to adsorb on the surface of halloysite, and generate CeOx nanoparticles after pyrolysis. Compared with CeO2 synthesized without adding HNTs, CeO2 nanoparticles in CeO2@HNTs are evenly dispersed on the surface of HNTs, and the size is reduced from 4.7nm to 2.8nm. This ultra-small CeO2 has a larger specific surface area, exposes more surface atoms, and has a higher Ce 3+ / Ce 4+ratio, showing enhanced nanozyme activity, which can effectively remove a variety of ROS. Chinese patent (publication number CN107308964A) discloses a method for preparing a halloysite-supported indium phosphate catalyst, specifically by using acid treatment to obtain a rough surface of halloysite, and using the adsorption effect between its rough surface and indium phosphate colloidal particles to load indium phosphate nanoparticles on the halloysite surface. These reported technologies mainly load nanoparticles on the outer surface of halloysite nanotubes, but nanoparticles are easy to fall off, have poor stability, and are difficult to recycle multiple times. A Chinese patent (publication number CN108059193A) discloses a method for preparing a ferroferric oxide nanocomposite material assembled in a halloysite tube, specifically, the halloysite nanotube is modified, Fe3O4 nanomagnetic particles are prepared by a mixed hydrothermal method, vacuum impregnation assembly, calcination, and finally the ferroferric oxide is assembled in the halloysite nanotube. This method loads ferroferric oxide nanoparticles in the halloysite nanotube, but it needs to synthesize ultrafine nano ferroferric oxide particles first, and then modify them in the halloysite nanotube. The process is very complicated, and it does not achieve in-situ loading of nano ferroferric oxide particles, and the stability of the material is poor.
[0003] Zirconium phosphate (ZrP) is a layered inorganic material that has attracted attention due to its high thermal stability and ultra-high acid and radiation resistance. ZrP crystals exist mainly in two forms, namely the thermodynamically stable α-form and the metastable γ-form. ZrP has been widely used in the adsorption of toxic metals, radioactive elements and rare earth elements due to its excellent ion exchange properties. However, in the actual application of existing zirconium phosphate materials, ZrP nanoparticles are mainly loaded on carriers such as activated carbon, silicates, biomass and polymers. However, it is difficult to in-situ generate zirconium phosphate nanoparticles with small particle size and uniform distribution on these carrier materials. At the same time, zirconium phosphate is easy to migrate and leach during use. Summary of the invention
[0004] In order to overcome the shortcomings and deficiencies of the prior art, the first object of the present invention is to provide a halloysite / zirconium phosphate nanocomposite material, which is composed of nano zirconium phosphate particles grown on the inner wall of halloysite nanotubes. The zirconium phosphate nanoparticles are small in size, evenly distributed, and have good load stability.
[0005] The second object of the present invention is to provide a method for preparing the halloysite / zirconium phosphate nanocomposite material, which is simple, has mild conditions and can be produced in large quantities.
[0006] The third object of the present invention is to provide an application of a halloysite / zirconium phosphate nanocomposite material, which exhibits high adsorption activity for heavy metal ions, can be widely used for the adsorption of heavy metal ions in a solution system, and has good stability and can be reused multiple times.
[0007] In order to achieve the above technical purpose, the present invention provides a halloysite / zirconium phosphate nanocomposite material, which is composed of nano zirconium phosphate particles grown on the inner wall of halloysite nanotubes.
[0008] The halloysite / zirconium phosphate nanocomposite material of the present invention fully utilizes the lumen space restriction effect of halloysite nanotubes to regulate the crystal size and distribution uniformity of zirconium phosphate nanoparticles and avoid their migration and leaching during use, thereby greatly improving the adsorption activity and recyclability of the composite material.
[0009] As a preferred solution, the size of the nano zirconium phosphate particles is 3-10 nm. Based on the fact that the nano zirconium phosphate particles are in-situ grown in the lumen of the halloysite nanotubes, they have uniform and small sizes, which greatly improves their activity.
[0010] The present invention also provides a method for preparing a halloysite / zirconium phosphate nanocomposite material, which comprises dispersing halloysite nanotubes in a solvent, adding a zirconium salt solution for ultrasonic treatment to obtain a halloysite-zirconium ion dispersion, subjecting the halloysite-zirconium ion dispersion to a cyclic vacuum treatment, and then separating the solid from the liquid. The obtained solid is placed in a phosphoric acid or phosphate solution for a phosphating reaction, and the obtained product is washed and dried to obtain the product.
[0011] The key to achieving in-situ growth of zirconium phosphate nanoparticles in halloysite nanotubes in the present invention is to utilize vacuum to promote the capillary action of the nanotubes and utilize the coordination effect of Al-OH on the inner tube wall of halloysite on zirconium ions, so as to introduce zirconium ions into the halloysite nanotubes and achieve in-situ growth of zirconium phosphate.
[0012] As a preferred solution, the zirconium ion concentration in the halloysite-zirconium ion dispersion is 0.1-10 mmol / L. If the zirconium ion concentration is too high, the particle size will be too large; if the zirconium ion concentration is too low, the halloysite lumen cannot be fully loaded.
[0013] As a preferred solution, the cyclic vacuum treatment conditions are: first evacuate to below -0.1 MPa, maintain stirring under vacuum for 30 to 120 minutes, then circulate to atmospheric pressure, and repeat this process 2 to 8 times. Under the preferred cyclic vacuum treatment conditions, zirconium ions can be uniformly infiltrated into the halloysite nanotubes.
[0014] As a preferred solution, the phosphate concentration in the phosphate solution is 0.5-2 mol / L.
[0015] As a preferred solution, the phosphating reaction conditions are: at room temperature, the reaction time is 6 to 24 hours. If the reaction time is too short, the phosphate solution cannot fully react with the zirconium ions in the halloysite tube; if the reaction time is too long, the size of the grown zirconium phosphate particles is too large.
[0016] The present invention also provides an application of the halloysite / zirconium phosphate nanocomposite material, which is used for adsorbing heavy metal ions in a solution system, and is particularly suitable for selectively adsorbing lead ions in a solution system.
[0017] The method for preparing the halloysite / zirconium phosphate nanocomposite material provided by the present invention comprises the following specific steps:
[0018] (1) Prepare 20 mL of a freshly uniformly dispersed 0.5 wt% to 2 wt% HNTs ethanol suspension, add a certain amount of 30 mL of zirconium oxychloride octahydrate (ZrOCl2.8H2O) solution thereto, and perform ultrasonic treatment for 30 to 60 min to obtain a uniformly dispersed halloysite-zirconium ion dispersion. Place the dispersion in a vacuum bottle, evacuate to below -0.1 MPa, stir under vacuum for 30 to 120 min, and then circulate to atmospheric pressure, repeating this process 3 times. The solvent of the ZrOCl2.8H2O solution is at least one of methanol, ethanol, ether, and acetone. The amount of ZrOCl2.8H2O should maintain the zirconium ion concentration in the dispersion at 0.1 to 10 mmol / L; preferably 1 mmol / L.
[0019] (2) The solid obtained in step (1) is placed in 100 mL of a 0.5-2 mol / L phosphoric acid solution for a certain period of time to promote the in-situ growth of ZrP nanoparticles. After the product is centrifuged, it is washed three times with ethanol and deionized water, and then freeze-dried to obtain a zirconium phosphate nanocomposite assembled in halloysite nanotubes. The phosphoric acid solution is at least one of phosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, and potassium dihydrogen phosphate. The reaction conditions are 6 to 24 hours at room temperature; preferably 12 hours. The centrifugation conditions are 6000 to 10000 rpm, 10 to 30 min; preferably 10000 rpm, 10 min.
[0020] Compared with the prior art, the technical solution of the present invention has the following advantages and effects:
[0021] 1) The halloysite / zirconium phosphate nanocomposite material provided by the present invention is composed of zirconium phosphate nanoparticles grown in situ in halloysite nanotubes. Based on the spatial confinement effect of the halloysite nanotubes, the zirconium phosphate particles can be made smaller in size and more evenly distributed, so as to have higher adsorption activity. In addition, the encapsulation of zirconium phosphate nanoparticles by the halloysite nanotubes inhibits the leaching and migration of ZrP that may occur during the adsorption process, thereby improving the recycling performance of the material.
[0022] 2) The halloysite / zirconium phosphate nanocomposite provided by the present invention converts the nonspecific adsorption of ions into specific adsorption due to the restriction effect of zirconium phosphate through the nanotube lumen, thereby improving the adsorption selectivity of zirconium phosphate.
[0023] 3) The preparation method of the halloysite / zirconium phosphate nanocomposite material provided by the present invention adopts a vacuum-assisted method, which can not only successfully modify the zirconium phosphate particles in the halloysite nanotubes, but also the synthesized zirconium phosphate particles are small in size and uniformly distributed. In particular, the zirconium phosphate nanoparticles are in-situ grown on the inner wall of the halloysite nanotubes and have good stability.
[0024] 4) The preparation method of the halloysite / zirconium phosphate nanocomposite material provided by the present invention is simple, the conditions are mild, and the halloysite is used as the substrate, which reduces the synthesis cost of the material and improves the environmental friendliness of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 TEM images of the halloysite / zirconium phosphate nanocomposite material and pure halloysite nanotubes prepared in Example 1.
[0026] Figure 2 This is a particle size distribution diagram of zirconium phosphate nanoparticles in the halloysite / zirconium phosphate nanocomposite material prepared in Example 1.
[0027] Figure 3 Zeta potential diagram of the halloysite / zirconium phosphate nanocomposite material prepared in Example 1 and pure halloysite nanotubes.
[0028] Figure 4 TGA characterization of the halloysite / zirconium phosphate nanocomposite and pure halloysite nanotubes prepared in Example 1.
[0029] Figure 5 The adsorption performance of the halloysite / zirconium phosphate nanocomposite material and pure halloysite nanotubes prepared in Example 1 was tested.
[0030] Figure 6 The selective adsorption performance of the halloysite / zirconium phosphate nanocomposite material and pure halloysite nanotubes prepared in Example 1 was tested. DETAILED DESCRIPTION
[0031] The following specific examples are intended to further illustrate the present invention rather than to limit the scope of protection of the claims.
[0032] Example 1
[0033] (1) 20 mL of a freshly prepared uniformly dispersed 1 wt% HNTs ethanol suspension was added to which 30 mL of a ZrOCl2·8H2O ethanol solution (containing 0.016 g ZrOCl2·8H2O) was added and ultrasonicated for 30 min to obtain a uniformly dispersed halloysite-zirconium ion dispersion. The dispersion was placed in a vacuum bottle, evacuated to -0.1 MPa, stirred for 60 min under vacuum, and then circulated to atmospheric pressure, and this process was repeated 3 times.
[0034] (2) The suspension of step (1) was centrifuged to obtain a solid, and the obtained solid was placed in 100 mL of 1 mol / L phosphoric acid solution for reaction for 12 h to promote the in-situ growth of ZrP nanoparticles. The product was centrifuged at 10000 rpm for 10 min, washed three times with ethanol and deionized water, and then freeze-dried to obtain the halloysite nanotube / zirconium phosphate nanocomposite.
[0035] In this embodiment, the particle size of zirconium phosphate is 4.0 nm.
[0036] Example 2
[0037] (1) 20 mL of a freshly prepared uniformly dispersed 0.5 wt% HNTs ethanol suspension was added to which 30 mL of ZrOCl2.8H2O ethanol solution (containing 0.032 g ZrOCl2·8H2O) was added and ultrasonicated for 30 min to obtain a uniformly dispersed halloysite-zirconium ion dispersion. The dispersion was placed in a vacuum bottle, evacuated to -0.1 MPa, stirred for 60 min under vacuum, and then circulated to atmospheric pressure. This process was repeated 3 times.
[0038] (2) The suspension of step (1) was centrifuged to obtain a solid, and the obtained solid was placed in 100 mL of 1 mol / L sodium dihydrogen phosphate solution for reaction for 12 h to promote the in-situ growth of ZrP nanoparticles. The product was centrifuged at 10000 rpm for 10 min, washed three times with ethanol and deionized water, and then freeze-dried to obtain the halloysite / zirconium phosphate nanocomposite material.
[0039] In this embodiment, the particle size of zirconium phosphate is 5.2 nm.
[0040] Example 3
[0041] (1) Prepare 20 mL of a freshly prepared uniformly dispersed 2 wt% HNTs ethanol suspension, add 30 mL of ZrOCl2.8H2O ethanol solution (containing 0.16 g ZrOCl2.8H2O), and ultrasonically treat for 60 min to obtain a uniformly dispersed halloysite-zirconium ion dispersion. Place the dispersion in a vacuum bottle, evacuate to -0.1 MPa, keep stirring under vacuum for 120 min, and then circulate to atmospheric pressure. Repeat this process 3 times.
[0042] (2) The suspension of step (1) was centrifuged to obtain a solid, and the obtained solid was placed in 100 mL of 2 mol / L potassium dihydrogen phosphate solution for reaction for 24 h to promote the in-situ growth of ZrP nanoparticles. The product was centrifuged at 10000 rpm for 30 min, washed three times with ethanol and deionized water, and then freeze-dried to obtain the halloysite / zirconium phosphate nanocomposite material.
[0043] In this embodiment, the particle size of zirconium phosphate is 6.3 nm.
[0044] Example 4
[0045] (1) 20 mL of a freshly prepared uniformly dispersed 0.5 wt% HNTs ethanol suspension was added to which 30 mL of a ZrOCl2.8H2O methanol solution (containing 0.0016 g ZrOCl2·8H2O) was added and ultrasonicated for 30 min to obtain a uniformly dispersed halloysite-zirconium ion dispersion. The dispersion was placed in a vacuum bottle, evacuated to -0.1 MPa, stirred for 60 min under vacuum, and then circulated to atmospheric pressure. This process was repeated 3 times.
[0046] (2) The suspension of step (1) was centrifuged to obtain a solid, and the obtained solid was placed in 100 mL of 1 mol / L phosphoric acid solution for 24 h to promote the in-situ growth of ZrP nanoparticles. The product was centrifuged at 10000 rpm for 10 min, washed three times with ethanol and deionized water, and then freeze-dried to obtain the halloysite / zirconium phosphate nanocomposite material.
[0047] In this embodiment, the particle size of zirconium phosphate is 9.2 nm.
[0048] Example 5
[0049] (1) 20 mL of a freshly prepared uniformly dispersed 1 wt% HNTs ethanol suspension was added to which 30 mL of ZrOCl2.8H2O ethanol solution (containing 0.016 g ZrOCl2·8H2O) was added and ultrasonicated for 30 min to obtain a uniformly dispersed halloysite-zirconium ion dispersion. The dispersion was placed in a vacuum bottle, evacuated to -0.1 MPa, stirred for 60 min under vacuum, and then circulated to atmospheric pressure. This process was repeated 3 times.
[0050] (2) The suspension of step (1) was centrifuged to obtain a solid, and the obtained solid was placed in 100 mL of 2 mol / L phosphoric acid solution for reaction for 12 h to promote the in-situ growth of ZrP nanoparticles. The product was centrifuged at 6000 rpm for 30 min, washed three times with ethanol and deionized water, and then freeze-dried to obtain the halloysite / zirconium phosphate nanocomposite material.
[0051] In this embodiment, the particle size of zirconium phosphate is 6.8 nm.
[0052] Example 6
[0053] (1) 20 mL of a freshly prepared uniformly dispersed 1 wt% HNTs ethanol suspension was added to which 30 mL of ZrOCl2.8H2O ethanol solution (containing 0.016 g ZrOCl2·8H2O) was added and ultrasonicated for 30 min to obtain a uniformly dispersed halloysite-zirconium ion dispersion. The dispersion was placed in a vacuum bottle, evacuated to -0.1 MPa, stirred for 60 min under vacuum, and then circulated to atmospheric pressure. This process was repeated 3 times.
[0054] (2) The suspension of step (1) was centrifuged to obtain a solid, and the obtained solid was placed in 100 mL of 1 mol / L phosphoric acid solution for reaction for 12 h to promote the in-situ growth of ZrP nanoparticles. The product was centrifuged at 10000 rpm for 10 min, washed three times with ethanol and deionized water, and then freeze-dried to obtain the halloysite / zirconium phosphate nanocomposite material.
[0055] In this embodiment, the particle size of zirconium phosphate is 4.7 nm.
[0056] Example 7
[0057] (1) 20 mL of a freshly prepared uniformly dispersed 2 wt% HNTs ethanol suspension was added to which 30 mL of ZrOCl2.8H2O acetone solution (containing 0.048 g ZrOCl2·8H2O) was added, and ultrasonic treatment was performed for 60 min to obtain a uniformly dispersed halloysite-zirconium ion dispersion. The dispersion was placed in a vacuum bottle, first evacuated to -0.1 MPa, stirred for 60 min under vacuum, and then circulated to atmospheric pressure. This process was repeated 3 times.
[0058] (2) The suspension of step (1) was centrifuged to obtain a solid, and the obtained solid was placed in 100 mL of 1 mol / L ammonium phosphate solution for 6 h to promote the in-situ growth of ZrP nanoparticles. The product was centrifuged at 10000 rpm for 30 min, washed three times with ethanol and deionized water, and then freeze-dried to obtain the halloysite / zirconium phosphate nanocomposite material.
[0059] In this embodiment, the particle size of zirconium phosphate is 8.9 nm.
[0060] Implementation effect description
[0061] The halloysite / zirconium phosphate nanocomposite material and pure halloysite nanotubes prepared in Example 1 were characterized by TEM. Figure 1 As shown. Figure 1 It can be seen that the inside of the pure halloysite nanotube is smooth, clean and free of impurities. In the prepared zirconium phosphate nanocomposite assembled in the halloysite nanotube, the zirconium phosphate is evenly distributed in the tube wall, and the synthesized zirconium phosphate has a smaller size.
[0062] The size statistics of the zirconium phosphate nanoparticles in the halloysite / zirconium phosphate nanocomposite prepared in Example 1 are as follows: Figure 2 As shown. Figure 2 It can be seen that the size of the zirconium phosphate particles is about 4.0±0.6 nm, and the zirconium phosphate has an ultrafine size.
[0063] The zeta potential of the zirconium phosphate nanocomposite material assembled in the halloysite nanotubes and the pure halloysite nanotubes prepared in Example 1 was characterized. Figure 3 As shown. Figure 3 It can be seen that compared with pure halloysite nanotubes, the halloysite / zirconium phosphate nanocomposite has a more negative Zeta potential. This change also means that the modified halloysite nanotubes will show a better adsorption effect on heavy metals.
[0064] The zirconium phosphate nanocomposite material assembled in the halloysite nanotubes prepared in Example 1 and the pure halloysite nanotubes were characterized by TGA. Figure 4 .Depend on Figure 4 It can be seen that the weight loss of the modified halloysite nanotubes is less than that of the pure halloysite nanotubes, which indicates that the halloysite nanotubes lose a portion of free water during the modification process, and the introduction of zirconium phosphate particles increases their mass.
[0065] The adsorption performance of the halloysite / zirconium phosphate nanocomposite and pure halloysite nanotubes prepared in Example 1 was tested. 25 mg of pure halloysite nanotubes or halloysite / zirconium phosphate nanocomposite was added to 50 mL of a 50 mg / L lead ion solution and then oscillated at 180 rpm for 72 s at 298 K to ensure equilibrium. During the entire adsorption process, 0.1 M HCl and 0.1 M NaOH were used to maintain the solution pH at about 5.0. The results are shown in FIG. Figure 5 As shown. Figure 5 It can be seen that the removal rate of lead ions by the prepared nanocomposite material is about 4.3 times that of pure halloysite nanotubes, and the modified halloysite nanotubes have excellent adsorption properties.
[0066] The selective adsorption performance of the halloysite / zirconium phosphate nanocomposite and pure halloysite nanotubes prepared in Example 1 was tested. Ca(NO3)2, which is commonly found in aquatic environments, was added to the test solution to investigate the adsorption of Ca(NO3)2. 2+Effect on the adsorption properties of materials. 25 mg of pure halloysite nanotubes or halloysite / zirconium phosphate nanocomposites were added to 50 mL of 50 mg / L lead ion and calcium ion solutions, with the ratios of lead ions to calcium ions set to 100%:0%, 80%:20%, 60%:40%, 40%:60%, and 20%:80% as controls, and then oscillated at 180 rpm for 72 at 298 K to ensure equilibrium. During the entire adsorption process, 0.1 M HCl and 0.1 M NaOH were used to keep the solution pH around 5.0.
[0067] Depend on Figure 6 It can be seen that with the increase of calcium ion concentration, the removal rate of lead ions by pure halloysite nanotubes drops sharply. However, the removal rate of lead ions by halloysite / zirconium phosphate nanocomposites remains above 75%, indicating that the adsorption of lead ions by halloysite / zirconium phosphate nanocomposites is mainly through coordination, which is a specific adsorption. Therefore, the presence of calcium ions has little effect on the adsorption capacity of halloysite / zirconium phosphate nanocomposites. Halloysite / zirconium phosphate nanocomposites have excellent selective adsorption capacity.
[0068] The present invention assembles a zirconium phosphate nanocomposite material in halloysite nanotubes, so that the size of the zirconium phosphate particles grows within an ultrafine range and can achieve highly uniform dispersion. The design of this structure not only brings significant advantages in the microscopic morphology of the material, but also gives the composite material a series of superior properties. First, since the zirconium phosphate particles have a larger specific surface area within the size range of the nanometer level, this improves its adsorption activity. Secondly, the nanotubular structure inside the composite material can provide more adsorption sites, thereby improving the total adsorption capacity of the material. Compared with traditional single adsorption materials, the synergistic effect of halloysite nanotubes and zirconium phosphate not only expands its adsorption capacity, but also makes the adsorption process more efficient. In addition, the structural design of the material is convenient for recycling after the adsorption process is completed.
Claims
1. A halloysite / zirconium phosphate nanocomposite material, characterized in that: It is composed of nano zirconium phosphate particles grown on the inner wall of halloysite nanotubes.
2. The halloysite / zirconium phosphate nanocomposite material according to claim 1, characterized in that: The size of the nano zirconium phosphate particles is 3.0-10 nm.
3. The method for preparing a halloysite / zirconium phosphate nanocomposite material according to claim 1, characterized in that: Halloysite nanotubes are dispersed in a solvent, and then a zirconium salt solution is added for ultrasonic treatment to obtain a halloysite-zirconium ion dispersion. The halloysite-zirconium ion dispersion is subjected to a cyclic vacuum treatment, and then the solid-liquid separation is performed. The obtained solid is placed in a phosphoric acid or phosphate solution for a phosphating reaction. The obtained product is washed and dried to obtain the product.
4. The method for preparing a halloysite / zirconium phosphate nanocomposite material according to claim 3, characterized in that: The zirconium ion concentration in the halloysite-zirconium ion dispersion is 0.1-10 mmol / L.
5. The method for preparing a halloysite / zirconium phosphate nanocomposite material according to claim 3, characterized in that: The conditions of the cyclic vacuum treatment are: first evacuate to below -0.1 MPa, maintain stirring under vacuum for 30 to 120 minutes, then circulate to atmospheric pressure, and repeat this process 2 to 8 times.
6. The method for preparing a halloysite / zirconium phosphate nanocomposite material according to claim 3, characterized in that: The phosphate concentration in the phosphate solution is 0.5-2 mol / L.
7. A method for preparing a halloysite / zirconium phosphate nanocomposite material according to claim 3 or 6, characterized in that: The conditions of the phosphating reaction are: reacting at room temperature for 6 to 24 hours.
8. Use of a halloysite / zirconium phosphate nanocomposite material according to claim 1 or 2, characterized in that: Used to adsorb heavy metal ions in solution systems.
9. The use of a halloysite / zirconium phosphate nanocomposite material according to claim 8, characterized in that: Used for selective adsorption of lead ions in solution systems.
Citation Information
Patent Citations
Preparation method of halloysite loaded indium phosphate catalyst
CN107308964A
Halloysite nanotube-ammonium phosphate composite material and preparation method and application thereof
CN103990429A
Method for preparing nanocomposite material by assembling ferriferrous oxide in halloysite tube
CN108059193A
Preparation method of halloysite-loaded zirconium oxide nano composite material
CN113842875A
Preparation method of zirconium phosphate confinement carbon nanotube material and application of zirconium phosphate confinement carbon nanotube material as adsorbent in In (III) ion adsorption
CN116902941A
Cited By
Preparation method and application of nano confinement zirconium phosphate biochar composite material
CN122252139A
Stone-impact-resistant and corrosion-resistant powder coating and preparation method thereof
CN122563453A
A stone chip resistant anticorrosive powder coating and a method of preparation
CN122563453B